Capicua deficiency induces autoimmunity and promotes follicular helper T cell differentiation via derepression of ETV5 - Sungjun Park (Nature Portfolio, 2017)
Follicular helper T (TFH) cells promote germinal centre (GC) response for efficient generation of protective antibodies during humoral immunity. Here the authors show that deficiency of the translational repressor, Capicua/CIC, enhances TFH differentiation and GC responses potentially via the derepression of Etv5.